Every scar tells a story: Insight into people's self-injury scar experiences. Issue 3 (2nd July 2016) - Lewis, Stephen P.; Mehrabkhani, Saba
Abstract : Scarring, a common and salient consequence of non-suicidal self-injury (NSSI), remains an under-explored issue in the field. Thus, the current investigation explored NSSI scar perspectives using online testimony from members of a popular NSSI message board; focus was attenuated to a series of message board posts pertinent to people's experiences with scars resulting from NSSI. Data (message board posts) were collected using the website's search function. A total of 53 posts involving discussion of people's NSSI scar perceptions and experiences were retained. A thematic analysis of the data indicated that individuals viewed their scars in a number of ways. Many viewed scars in a resilient manner, often in the context of a self-narrative. Others, however, were unaccepting of their scars (e.g. expressed feelings of shame, hatred, or disgust). For some, they were able to gradually accept their scars but only after a period of difficulty. And, finally, some individuals expressed mixed feelings toward their scars (e.g. a love/hate relationship). Hence, scars stemming from NSSI seem to differentially impact individuals who self-injure. Possible implications for research and clinical practice are discussed.